Pengaruh Socio Economic, Entrepreneurship dan Motivasi Mahasiswa Terhadap Pembelajaran Bisnis Internasional Berbasis Project Dimediasi Self-Efficacy - Romauli Nainggolan; Yuli Kartika Dewi; Junko Alessandro Effendy (Fakultas Ekonomi, Universitas Ekasakti, 2025)
Project-based learning is one of the learning methods that is widely favored in schools and universities. So, it is important to study how much impact this method has in terms of student learning experience. Project-based learning involves many students in interactive impacts. This study is a quantitative study with the aim of studying the impact of socioeconomic variables, entrepreneurship, and student learning motivation on the success of learning International Business courses based on projects mediated by the self-efficacy variable. This study will answer 10 hypotheses. The analysis technique uses the Structure Equation Model (SEM). The population is second-semester students in the Management study program who take International Business courses with project-based learning methods. The data collection method uses a questionnaire distributed to 270 student respondents. The tools used are SEM-PLS. The results of this study reveal that self-efficacy is able to moderate the influence of socioeconomic, entrepreneurship, and student learning motivation on the success of Learning International courses based on Projects. The results of this study reveal three interesting things. First, learning motivation has a positive effect on self-efficacy. Second, self-efficacy has an effect on project-based learning. Third, self-efficacy can mediate students' learning motivation toward project-based learning. This means that the higher the learning motivation, the greater the impact on learning outcomes. Therefore, it is important for educators to provide motivational support to students so that learning objectives are achieved.